2018
DOI: 10.1071/mf18120
|View full text |Cite
|
Sign up to set email alerts
|

Safe two-way migration for salmonids and eel past hydropower structures in Europe: a review and recommendations for best-practice solutions

Abstract: This review provides a summary of knowledge on two-way fish migration of salmonids and eels past hydroelectric plants in Europe. On the basis of a summary of international literature, general designs and recommendations for best practices for fish-pass facilities are provided. The review is part of the Norwegian SafePass project, which focuses on Atlantic salmon, brown trout, grayling and European eel. According to recent international recommendations, many existing European fishways for upstream migration do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…Roscoe et al (2011) found reduced survival of Sockeye salmon ( Oncorhynchus nerka ) that had traversed a dam relative to those that did not and suggested energetic costs of the dam passage as a possible mechanism for this. Additional energetic costs may also arise if passing the dam results in migration delays (Fjeldstad et al 2018), and particularly if such delays forced individuals to overwinter in the river instead of the lake as has been observed in our population. Since energy reserves scale positively with body size (Peters and Peters 1986) such energetic costs may be heavier for smaller individuals, possibly contributing to the negatively size-dependent background mortality predicted by the model.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Roscoe et al (2011) found reduced survival of Sockeye salmon ( Oncorhynchus nerka ) that had traversed a dam relative to those that did not and suggested energetic costs of the dam passage as a possible mechanism for this. Additional energetic costs may also arise if passing the dam results in migration delays (Fjeldstad et al 2018), and particularly if such delays forced individuals to overwinter in the river instead of the lake as has been observed in our population. Since energy reserves scale positively with body size (Peters and Peters 1986) such energetic costs may be heavier for smaller individuals, possibly contributing to the negatively size-dependent background mortality predicted by the model.…”
Section: Discussionmentioning
confidence: 82%
“…On many hydroelectric dams - including the Hunderfossen dam - racks are installed in front of turbine intakes to prevent downriver migrating fish from entering and being exposed to high turbine mortality ( e.g. Fjeldstad et al 2018, Haraldstad et al 2018). The effectiveness of such racks varies across species and sizes, but they appear to work relatively well for adult salmonids (Calles et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abrupt changes in light intensity such as at the entrance/exits of fishways or culverts can also cause avoidance behaviour in lampreys (Moser and Mesa 2009) and juvenile salmon (Ono and Simenstad 2014). However, other studies have demonstrated that upstream migrating salmon, trout, eels, Topeka Shiner, Fathead Minnow and common galaxias in Australia, are unaffected by reduced light levels in civil structures (Fjeldstad et al 2018; Amtstaetter et al 2017; Kozarek et al 2017; Gowans et al 2003; Rogers and Cane 1979). These conflicting accounts of the effect of light on fish movement suggest a range of species-specific behavioural responses to different lighting conditions (Fjeldstad et al 2018; Amtstaetter et al 2017; Kozarek et al 2017; Gowans et al 2003; Rogers and Cane 1979), with such variability also indicating that our understanding of the effects of altered lighting regimes on fish movement is poor, despite this issue being raised in several fish passage guidelines (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…In the Netherlands, discharge sluices and large pumping stations have been built for water level control of the catchment areas, protection against the sea and to limit saltwater intrusion. Fish migration can be hampered by pumping stations by inducing additional mortality when the turbines are not designed in a fish‐friendly manner (Buysse, Mouton, Baeyens, & Coeck, 2015; Fjeldstad, Pulg, & Forseth, 2018) or by delaying fish resulting in additional energy loss and potential mismatch in arrival time on spawning grounds affecting reproductive success and fitness (Fjeldstad et al, 2018; Travade, Larinier, Subra, Gomes, & De‐Oliveira, 2010; Verhelst, Baeyens, et al, 2018). The delay in migration could also result in higher predation and fishing risk, higher risk of contracting diseases (Calles et al, 2010; Jansen, Winter, Bruijs, & Polman, 2007; Lennox, Økland, Mitamura, Cooke, & Thorstad, 2018; Verhelst, Buysse, et al, 2018) or eel could postpone their migration (Durif, Dufour, & Elie, 2005; Jansen et al, 2007; Winter, Jansen, & Bruijs, 2006).…”
Section: Introductionmentioning
confidence: 99%